The echo of Odin : Norse mythology and human consciousness - Smith, Edward W. L. (McFarland and Company, Inc., 2018)
"This book presents the cosmography of Norse mythology as a landscape of human inner life. Each of the nine worlds of this cosmography is viewed as a symbol of a distinct type of consciousness. The philosophy of pagan mythology is explored by comparing and contrasting the Sayings of Odin from the Norse Edda with the Christian Ten Commandments"--